Prediction of mortality in NICU of tertiary care rural hospital by using Snappe- II - Chaudhary , Shruti; Varma, Ashish (International Journal of Psychosocial Rehabilitation, 2020)
Neonatal mortality is very high in India. The complains of neonatal illnesses are not that obvious, so by the time an illness is diagnosed, the neonates become critically ill. Hence, an objective scale is required. To predict mortality of neonates in NICU by using SNAPPE II. To study correlation of snappe II score and mortality of neonates. The study was conducted in Neonatal ICU of Jawaharlal Neharu Medical College and AVBRH ,Sawangi (M) , WardhaDuration of study: 2 years .From August 2018 to June 2020Sample size : 50Type of study : Prospective observational studyEthical Committee approval : The Institutional Ethical Committee permission was sought to conduct this study before data collection.Inclusion criteria : All newborns coming to NICU with birth weight < 1500 gm Exclusion criteria :Neonates going discharged against medical advice and referred patients.Congenital malformationsProcedure of study : All patients getting admitted to NICU with